Safety and immunologic effects of IL-15 administration in nonhuman primates - Berger, Carolina (American Society of Hematology, 2009)
The administration of cytokines that modulate endogenous or transferred T-cell immunity could improve current approaches to clinical immunotherapy. Interleukin-2 (IL-2) is used most commonly for this purpose, but causes systemic toxicity and preferentially drives the expansion of CD4(+)CD25(+)Foxp3(+) regulatory T cells, which can inhibit antitumor immunity. IL-15 belongs to the γ(c) cytokine family and possesses similar properties to IL-2, including the ability to induce T-cell proliferation. Whereas IL-2 promotes apoptosis and limits the survival of CD8(+) memory T cells, IL-15 is required for the establishment and maintenance of CD8(+) T-cell memory. However, limited data are available to guide the clinical use of IL-15. Here, we demonstrate in nonhuman primates that IL-15 administration expands memory CD8(+) and CD4(+) T cells, and natural killer (NK) cells in the peripheral blood, with minimal increases in CD4(+)CD25(+)Foxp3(+) regulatory T cells. Daily administration of IL-15 resulted in persistently elevated plasma IL-15 levels and transient toxicity. Intermittent administration of IL-15 allowed clearance of IL-15 between doses and was safe for more than 3 weeks. These findings demonstrate that IL-15 has profound immunomodulatory properties distinct from those described for IL-2, and suggest that intermittent administration of IL-15 should be considered in clinical studies.